Long Range Channel Characteristics Through Foliage - Binti Masadan, Nurul Afifah; Hadi Habaebi, Mohamed; Hajar Yusoff, Siti (Bulletin of Electrical Engineering and Informatics, 2019)
Long Range Low Power Wide Area Network (LoRa LPWAN) technology is unique and remarkable technology because of its long-range coverage, low power consumption and low cost system architecture. These features have allowed Lora LPWAN to become a favorable option for performing communication in most of IoT wireless applications. In this paper, the foliage effect has been studied in terms of attenuation and its overall contribution to the path-loss and link budget calculations.  Specifically, 5 tree types were studied and their contribution to the path loss were quantified for different path crossings (e.g., trunk, tree-top and branches). The trees are Licuala Grandis, Mimusops Elengi, Mangifera Indica, Cyrtostachys Renda and Livistona Chinensis. Mimusops Elengi tree gave the strongest mean foliage attenuation accumulating up to 20 dB, due to its big size and crown density. Trunks contribute even higher attenuation in comparison to tree-tops and branches. The Okumura/Hata, Log-normal shadowing and foliage models are used as references for this propagation models development in this paper. Our study showed that Okumura fails to capture the effect of foliage in an environment rich in trees and biodiversity. This demonstrates the need for considering the tropical environment where the characterization of foliage attenuation plays an important role in determining the propagation model path-loss and link budget needed for network design and planning.